Side‐by‐side versus stent‐in‐stent technique for stent deployment during systemic chemotherapy in biliary tract cancer patients with malignant hilar biliary obstruction - Shunsuke Imamura; Kazuo Watanabe; Kanae Inoue; Tomonao Taira; Taro Shibuki; Tomoyuki Satake; Shota Yamaguchi; Mitsuhito Sasaki; Hiroshi Imaoka; Shuichi Mitsunaga; Masafumi Ikeda (DEN Open)
Abstract Objectives With the improved prognosis of patients with biliary tract cancer (BTC) owing to advances in chemotherapy, long‐term stent patency has become an important goal in patients undergoing biliary stent placement. We compared the duration of stent patency between unresectable BTC patients undergoing multi‐stenting for malignant hilar biliary obstruction by the side‐by‐side (SBS) and stent‐in‐stent (SIS) techniques during systemic chemotherapy. Methods We retrospectively evaluated the data of 62 unresectable BTC patients who underwent multi‐stenting before the first or second cycle of first‐line chemotherapy. Stent deployment was performed by the SBS technique in 40 patients (SBS group) and by the SIS technique in 22 patients (SIS group). Results The median time‐to‐recurrent biliary obstruction was 147 days in the SBS group and 252 days in the SIS (p = 0.029), being longer in the SIS group. The rates of development of early adverse events were 28% and 9% (p = 0.09) and the rates of development of late adverse events were 26% and 14% in the SBS and SIS groups (p = 0.27). The median overall survival was 480 days in the SBS group and 563 days in the SIS group (p = 0.92). Conclusion The duration of stent patency was shorter in the SBS group than in the SIS group; thus, the SIS technique is preferable to the SBS technique for biliary stent deployment in unresectable BTC patients during systemic chemotherapy.